Novel Muntingia Calabura bark fiber reinforced green-epoxy composite: A sustainable and green material for cleaner production. (20th April 2021) - Vinod, A.; Yashas Gowda, T.G.; Vijay, R.; Sanjay, M.R.; Gupta, Munish Kumar; Jamil, Muhammad; Kushvaha, Vinod; Siengchin, Suchart
Abstract: This study focuses on the development and property enhancement of novel Muntingia calabura bark micro-fiber reinforced bio-epoxy composite through surface modification techniques using NaOH and silane. The proposed novel plant fiber was extracted from an agro-waste after the tree's lifespan which was causing landfill. The performance characteristics of the developed composites were evaluated through physico-chemical and thermomechanical analysis. These fibers are subjected to chemical and physical analysis, while the composites are subjected to their mechanical, thermal, thermomechanical, and viscoelastic performance. The results revealed that the silane and NaOH modification of fiber reduced the fiber diameter by 9.17% and 17.43%; improved crystalline index by 41.01% and 14.86%; improved thermal stability by 14.15% and 4.81%; and increased the tensile strength by 37.75% and 28.92%. The complete analysis revealed silane treatment was the best for Muntingia Calabura micro-fiber compared to NaOH treatment and using raw fibers. Finally, based on improved results, this novel plant fiber was identified as a potential resource of environmentally friendly and sustainable raw material for reinforcement in polymer composites, which can be used to develop the green composites for lightweight structural applications.